Emotional Storytelling in the Classroom: Individual versus Group Interaction between Children and Robots - Leite, Iola; McCoy, Marissa; Lohani, Monika; Ullman, Daniel; Salomons, Nicole; Stokes, Charlene; Rivers, Susan; Scassellati, Brian (Hri '15: ACM/IEEE International Conference on Human-Robot Interaction USB Stick, 2015)
Robot assistive technology is becoming increasingly prevalent. Despite the growing body of research in this area, the role of type of interaction (i.e., small groups versus individual interactions) on effectiveness of interventions is still unclear. In this paper, we explore a new direction for socially assistive robotics, where multiple robotic characters interact with children in an interactive storytelling scenario. We conducted a between-subjects repeated interaction study where a single child or a group of three children interacted with the robots in an interactive narrative scenario. Results show that although the individual condition increased participant's story recall abilities compared to the group condition, the emotional interpretation of the story content seemed more dependent on the difficulty level rather than the study condition. Our findings suggest that, despite the type of interaction, interactive narratives with multiple robots are a promising approach to foster children's development of social-related skills.